PEMBERDAYAAN UMKM BERBASIS INOVASI PEMUTIHAN BERAS DAN PENDAMPINGAN MANAJEMEN UNTUK MENINGKATKAN KUALITAS PRODUK, LEGALITAS USAHA, SERTA KETAHANAN PANGAN DI KABUPATEN KEBUMEN - Pramudi, Ganjar; Rovianto, Eki; Adika, Dimas (Universitas Mataram, 2025)
Prima Oryza Abadi, a small rice milling and sales business in Krandegan Village, Kebumen Regency, faces challenges in product quality and business legality that limit its competitiveness and business growth. The rice produced has a cloudy color, low cleanliness levels, and many broken grains, resulting in a selling price of only around IDR 11,000–13,000 per kg, far below the market potential of IDR 17,000/kg if quality were improved. In addition, the lack of business licenses, trademarks, and legal entities makes it difficult for partners to access capital, establish cooperation, and build consumer trust. The objective of this program is to increase business capacity and competitiveness through product quality improvement, operational efficiency, and strengthening of legality-based business management. The methods used include socialization, training in rice whitening machine technology, the application of technological innovations with a capacity of 150 kg/hour with a steam atomization system, air drying, and low-speed milling, as well as assistance in obtaining a Business Identification Number (NIB), PIRT Certificate, trademark at the National Intellectual Property Agency (DJKI), and the establishment of a legal entity (UD). The results show a significant improvement in rice quality, as seen in whiter color, better cleanliness, and fewer damaged or broken grains. The machine is capable of efficiently processing 150 kg of rice per hour without the use of chemicals, thus meeting food safety standards. Partners have successfully registered trademarks and obtained complete business legality, enabling direct sales to consumers and market expansion. Management assistance also improved financial management and digital marketing capabilities. Overall, the program successfully improved product quality, competitiveness, and business sustainability, while supporting 2 and 8 and strengthening the local economy.